Farmer's Perception Toward Management Of Zakat At Karang Duwur Village, Petanahan, Kebumen, Central Java: Proceed. 2nd UMY-IIUM International Joint Seminar - Triyono, Siti Yusi Rusimah; dkk (UMY & IIUM, 2009)
Farmer's Perception Toward Management Of Zakat At Karang Duwur Village, Petanahan, Kebumen, Central Java